Integrating Human Resource Management and Islamic Leadership to Improve Civil Servant Performance - Zulkifli Zulkifli; Thamrin Kamal; Julhadi Julhadi; Syafnan Syafnan; Ramza Fatria Maulana (International Journal of Educational Narratives, 2026)
Background: The performance of State Civil Apparatus (ASN) in religious-based public institutions requires an integrated approach that combines professional human resource management with Islamic leadership values. Initial observations at the Office of the Ministry of Religious Affairs, Solok Regency, revealed gaps in competency, discipline, and service quality. Purpose: This study aims to analyze the integration of human resource management and Islamic leadership in improving ASN performance, with work motivation as a mediating variable. Method: A quantitative correlational approach with a survey method was employed. A sample of 244 ASN was selected from a population of 769 using Slovin’s formula and simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) based on AMOS 26. Results: The findings indicate that HRM has a positive and significant effect on work motivation (? = 0.412; p < 0.001) and ASN performance (? = 0.287; p = 0.002). Islamic leadership also positively and significantly affects work motivation (? = 0.356; p < 0.001) and ASN performance (? = 0.294; p = 0.003). Work motivation significantly influences ASN performance (? = 0.478; p < 0.001) and serves as a partial mediator in both relationships, with mediation proportions of 40.7% and 41.0%, respectively. Conclusion: The integration of effective HRM and strong Islamic leadership significantly enhances ASN work motivation and performance. This model proves empirically valid for fostering professional, integrity-driven, and spiritually grounded public services within the Ministry of Religious Affairs. Strengthening merit-based HR systems and Islamic leadership qualities such as trustworthiness, justice, deliberation, and role-modeling is essential for sustainable ASN performance improvement.